Romantik Journal for the Study of Romanticisms (Edition 1) - Smith, Troy Wellington (2019)
"Romantik. Journal for the Study of Romanticisms" is a multidisciplinary journal dedicated to the study of romantic-era cultural productions and concepts. The journal promotes innovative research across disciplinary borders. It aims to advance new historical discoveries, forward-looking theoretical insights and cutting-edge methodological approaches. The articles range over the full variety of cultural practices, including the written word, visual arts, history, philosophy, religion, and theatre during the romantic period (c. 1780-1840). But contributions to the discussion of pre- or post-romantic representations are also welcome. Since the romantic era was characterized by an emphasis on the vernacular, the title of the journal has been chosen to reflect the Germanic root of the word. But the journal is interested in all European romanticisms - and not least the connections and disconnections between them - hence, the use of the plural in the subtitle. Romantik is a peer-reviewed journal supported by the Nordic Board for Periodicals in the Humanities and Social Sciences (NOP-HS).